Effectivity Improving Chemistry Laboratory Literacy Levels Through The Development of e-EncyLab Using 3D Pageflip Professional - Linawati, Linawati; Noer, Asmadi M.; Anwar S, Lenny; Holiwarni, Betty (JTK (Jurnal Tadris Kimiya), 2024)
This research aims to determine the effectiveness of chemistry laboratory literacy levels by developing an e-EncyLab using 3D Pageflip Professional. This study employs a quantitative research methodology. The participants were 10th-grade students. Data was collected using a set of 12 essay questions designed to assess chemistry laboratory literacy, available in the e-EncyLab. Increasing laboratory literacy level abilities can be determined using the N-gain test. The results of this research showed an increase in N-Gain of 0.68 in the medium category. The effect of using e-EncyLab in increasing chemistry laboratory literacy is shown by the results of the paired sample test, which shows sig 0.000 < sig 0.05, which means there is a significant difference in the level of chemistry laboratory literacy of students in the control class and the experimental class that uses e-EncyLab. The use of e-EncyLab is effective in increasing students' chemistry laboratory literacy.